Implementasi Strategik Program Kota Tanpa Kumuh (Kotaku) Pada Kantor Badan Perencanaan Pembangunan Daerah Kota Makassar (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study purposed to find out how the strategy of the regional development planning agency in implementing the city without slum program (KOTAKU) in Makassar City Regional development  planning agency. The number of informants in this study was 7 people. The results showed that the strategic implementation of city program without slums (KOTAKU)  at the Makassar city regional development planning agency office was already running in accordance with the applicable standard operating program procedures. This seen from the four indicators, namely effectiveteness and efficiency, organizational  structure, leadership, motivation, in this case the city program hadbbeen implemented in 127 villages in Makassar based on criteria, namely light slum, moderate slum, and heavy slum. The implementation of the program by the Makassar city regional Development planning agency related to the KOTAKU program had been running since the begining of 2015 until now and had entered the 60% achievement that carried out well. Keywords: Implementation of strategy, city program without slum (KOTAKU)